Adverse selection and risk adjustment under imperfect competition - Normann Lorenz (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2013)
This paper analyzes the distortions of health insurers benefit packages due to adverse selection when there is imperfect competition. Within a discrete choice setting with two risk types, the following main results are derived: For intermediate levels of competition, the benefit packages of both risk types are distorted in the separating equilibrium. As the level of competition decreases, the distortion decreases for the low risk type, but increases for the high risk type; in addition, the number of insurers offering the benefit package for the low risk type increases. If the level of competition is low enough, a pooling equilibrium emerges, which generally differs from the Wilson-equilibrium. It is shown that these results have important implications for risk adjustment: For intermediate levels of competition, risk adjustment can be ineffective or even decrease welfare if it is not reasonably precise.
Keywords: I18; 330; Adverse selection; discrete choice; risk adjustment